Pengaruh Peningkatan Indikator Pendidikan Terhadap Kedalaman Kemiskinan dengan Belanja Modal Pendidikan Sebagai Variabel Moderasi - Abimanyu, Fachryza; Rustam, Rinaldi; Sutrisno, Mona Adriana (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study analyzes the effect of Average Years of Schooling (RLS), Smart Indonesia Program (PIP), and Smart Indonesia College Card (KIP-K) on the Poverty Depth Index (IKK) in the Rebana area of ​​West Java with Education Capital Expenditure (BMP) as a moderating variable. The method used is panel data regression and Moderated Regression Analysis (MRA) with 2017–2024 time series data and cross-sections from 7 regencies/cities. The results show that RLS, PIP, and BMP have a significant negative effect on IKK, while KIP-K has a positive but insignificant effect. The moderation test shows that BMP is unable to moderate the effect of RLS on IKK, but significantly moderates the effect of PIP. Meanwhile, BMP is unable to moderate the effect of KIP-K on IKK.